Reviving Classical Liberalism Against Populism - Karlson, Nils (Palgrave Studies in Classical Liberalism,, 2024)
"One cannot fight the collectivistic identity politics of populism with cost-benefit studies and policy analysis alone. As Nils Karlson argues in his riveting, essential book, the arts, and the humanities, "emotions. . . ethos . . . narratives," are necessary to save us from 1984 in 2024." ---Deirdre McCloskey, Professor emerita of Economics, History, English, And Communication, University of Illinois at Chicago, USA "Classical liberalism is better than populism, flat out. Nils Karlson will tell you why, both for the US and Sweden, and for the broader world." ---Tyler Cowen, Professor of Economics, George Mason University, USA This open access book by Nils Karlson explores the strategies used by left- and right-wing populists to make populism intelligible, recognizable, and contestable. It presents a synthesized explanatory model for how populists promote autocratization through the deliberate polarization of society. It traces the ideational roots of the core populist ideas and shows that these ideas form a collectivistic identity politics. Karlson argues that to fight back requires the revival of liberalism itself by defending and developing the liberal institutions, the liberal spirit, liberal narratives, and liberal statecraft.  The book also presents and discusses an extensive list of counterstrategies against populism.  Written within the tradition of political theory and institutional economics, this book uses a wide variety of sources, including results and analyses from social psychology, ethics, law, and history. Nils Karlson is the founder and former CEO of the Ratio Institute in Stockholm, Sweden. .